Basic skills examination in a biochemical practical training program for undergraduate students. Issue 3 (4th March 2019) - Sakiyama, Haruhiko; Eguchi, Hironobu; Yoshihara, Daisaku; Ookawara, Tomomi; Naruse, Hitoshi; Fujiwara, Noriko; Suzuki, Keiichiro
Abstract: University lectures are mainly passive in nature, and there are few subjects in which students need to learn and function independently. Tutorial education and related activities at universities that specialize in medical and pharmaceutical training have been actively carried out, and lectures in conjunction with practical skills are gradually being developed, although progress has been slow in this area. In past years, our biochemistry practice classes have been evaluated in reports dealing with experiments and written examinations, as is done in other universities. However, using this methodology, we are not able to evaluate the extent to which students master biochemical experimental skills. To address this, we introduced a basic skill test to our biochemical curriculum for the first time. Our exams contributed to a deeper understanding of student skills and could be good tools for evaluating the degree of understanding of the students. The students understood the contents of the training well and felt interested in research in the field of basic medicine. Thus, we conclude that introducing practical testing to biochemical practice was effective for medical students in the field of biochemistry. © 2019 International Union of Biochemistry and Molecular Biology, 47(3):279–287, 2019.